Inhibitory effect of probiotic Lactobacillus supernatants from the oral cavity on Streptococcus mutans biofilms. (October 2018) - Rossoni, Rodnei Dennis; Velloso, Marisol dos Santos; de Barros, Patrícia Pimentel; de Alvarenga, Janaina Araújo; Santos, Jéssica Diane dos; Santos Prado, Ana Carolina Chipoletti dos; Ribeiro, Felipe de Camargo; Anbinder, Ana Lia; Junqueira, Juliana Campos
Abstract: Probiotics can release bioactive substances that can inhibit the growth and biofilm formation of pathogenic microorganisms such as Streptococcus mutans . In this context, we evaluated whether the supernatants of Lactobacillus strains isolated from caries-free subjects can inhibit S. mutans, one of the most important bacteria for dental caries. First, the supernatants of 22 Lactobacillus strains were screened for antibacterial activity against S. mutans in planktonic cultures. All 22 Lactobacillus strains studied (100%) showed antibacterial activity. Thereafter, the Lactobacillus strains with the greatest reductions in the planktonic S. mutans cultures were tested on biofilms. The L. fermentum 20.4, L. paracasei 11.6, L. paracasei 20.3 and L. paracasei 25.4 strains could significantly reduce the number of S. mutans cells in biofilms formed in hydroxyapatite ( p < 0.05). This reduction was also confirmed by scanning electron microscopy analysis and was not caused by the decreased pH value in the medium ( p > 0.05). In addition, the supernatants of these probiotic strains could also reduce the total biomass of S. mutans biofilms ( p < 0.05). In conclusion, most of the Lactobacillus strains tested have some antibacterial activity against S. mutans . L. fermentum 20.4, L. paracasei 11.6, L. paracasei 20.3 and L. paracasei 25.4 produce bioactive substances that caused a significant reduction in S. mutans biofilms. Graphical abstract: Highlights: Oral cavities of healthy individuals may harbor some beneficial Lactobacillus strains. Probiotics can release bioactive substances that are able to inhibit S. mutans. Probiotics contribute to the development of new agents to prevent dental caries. L. paracasei strain 25.4 has the potential for clinical studies.